DI-093 Asymmetry of adverse drug reactions distribution between male and female patients with multiple myeloma treated with lenalidomide. (24th February 2014) - Scaldaferri, M; Calvo, C; Barilà, D; Re, F; Sciorsci, E; Fantozzi, R; Stecca, S; Azzolina, MC; Arione, R; Cattel, F
Abstract : Background: Lenalidomide has a complex mechanism of action which can result in a wide range of adverse reactions, due to its effects on the cytokine network. Purpose: To check the possibility of asymmetric distribution of Adverse Drug Reactions (ADRs) between male and female patients treated with lenalidomide for Multiple Myeloma (MM) at our Haematology Centre. Materials and methods: ADR reports were extracted from the Italian 'Registro Farmaci Oncologici AIFA' on 30/06/2012 and from medical records. The chi-squared test was applied to determine p-values for the differences in ADRs between male and female patients. Results: Among 75 relapsed MM patients, 55 (73%) had at least one ADR and 17 (23%) stopped the treatment because of ADRs. The total number of alerts was 209. The more frequent reports were for blood/lymphatic system disorders (LINF), for administration-related disorders (GEN) and for respiratory disorders (RESP). Sixty-six% of reports involved female patients. In the three more frequent ADR categories, the distribution was: LINF 26.39% of ADRs in male patients vs. 35.04% of ADRs in female patients (p = 0.18); GEN 30.56% of ADRs in male patients vs. 17.52% of ADRs in female patients (p = 0.03), RESP 4.17% of ADRs in male patients vs. 13.87% of ADRs in female patients (p = 0.01). Among 15 refractory MM patients, 83% of ADR reports involved male patients. Conclusions: In both groups, asymmetry was found in the distribution of ADRs between male and female patients, with discordant general trends. ADRs were more frequent in female patients in the relapsed MM group and, conversely, in male patients in the refractory MM group. In the relapsed MM group, LINF and RESP disorders were more frequent in female patients, while in both groups, the GEN disorders were more frequent in male patients. We will investigate whether these differences result from an ADR reporting bias or from gender heterogeneity in lenalidomide tolerability. No conflict of interest.